Pembangunan Sistem Informasi Praktik Pengalaman Lapangan (PPL) Berbasis Android (Studi Pada Fakultas Ilmu Komputer Universitas Brawijaya) - Rizky Wahyu Setiawan; Satrio Agung Wicaksono; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Pedagogic competence is the main of terms that must be had for a teacher. in Information Technology Education Program Study, Faculty of Computer Science Brawijaya University, obligate their students to do Educational Field Experience Placement to equip their graduates become a teacher. PPL has several part, they are Registration of PPL, Practice PPL I, Practice PPL II, and PPL Report. However, the information system for this program has not supported yet in Faculty of Computer Science at the same time. So that, the activity of PPL become less effective. According to that problem, this research aim to develop an information system that can support process PPL for every stakeholder. The system that will be developed having four features, they are Registration PPL for student, Record Logbook for student, Approve Logbook for teacher, and Assessment PPL for teacher. This system will be developed using Android platform for increase portability and accesibility of system. In this development is used metodology Extreme Programming. Then system will be tested using Black Box and Mobile (Android Platform) Compatibility Testing. The result shows that the system is 100% valid and 100% compatible.